Comparing three different anti-PD-L1 antibodies for immunohistochemical evaluation of small cell lung cancer. (November 2019) - Yoshimura, Akihiro; Yamada, Tadaaki; Miyagawa-Hayashino, Aya; Sonobe, Yuta; Imabayashi, Tatsuya; Yamada, Takahiro; Okada, Satoru; Shimamoto, Takayuki; Chihara, Yusuke; Iwasaku, Masahiro; Kaneko, Yoshiko; Uchino, Junji; et al.
Highlights: Factor affecting response to SCLC is unknown. Multi-antibodies for PD-L1 are similar results in SCLC. PD-L1 tends to associate with serum NSE. Abstract: Objective: Small cell lung cancer (SCLC), which accounts for approximately 15% of all lung cancer cases, has high initial sensitivity to chemotherapy. However, clinical outcomes have not improved in the past two decades. Therefore, novel biomarkers are needed to prolong survival in patients with advanced SCLC. Material and methods: In this retrospective study, we assessed 44 patients with SCLC who underwent first-line or adjuvant chemotherapy. We analyzed PD-L1 expression in SCLC tumors using three specific anti-PD-L1 antibody clones (28-8, 22C3, and SP263) and assessed their correlation with clinical profiles. Results: Each clone yielded PD-L1 positivity as follows: 10 cases with 28-8, eight cases with 22C3, and six cases with SP263. Eleven patients tested positive with at least one of the three anti-PD-L1 antibodies, and 33 patients tested negative with all anti-PD-L1 antibodies. Serum neuron-specific enolase levels at diagnosis were significantly higher in negative tumors than in positive tumors with the 28-8 clone (p = 0.036) and, similarly, tended to be higher in negative tumors with the 22C3 and SP263 clones. Conclusion: These observations suggest that PD-L1 is detected in SCLC tumors at a similar rate and with similar clinical correlates when detected using any of these three anti-PD-L1 clones. Further large-scale investigations are warranted to reveal the roles of PD-L1 expression in patients with SCLC.